Biological significance of piRNA in liver cancer: a review. (17th August 2020) - Xu, Jiamin; Yang, Xi; Zhou, Qing; Zhuang, Jing; Han, Shuwen
Abstract: Liver cancer is one of the most common and deadly cancers in the world. In recent years, non-coding RNA has been a hot topic in liver cancer research. piRNAs (PIWI-interacting RNAs) are a new type of small non-coding RNA, which are formed by the PIWI proteins interacting with RNA. The latest research shows that piRNA and PIWI proteins are abnormally expressed in various cancers, including pancreatic, colorectal, breast, etc. piRNA plays an important regulatory role in liver cancer. In this review, we discuss the biological function of piRNAs and new progress in the development of liver cancer, and new targets and ideas for piRNA and PIWI proteins in the diagnosis and treatment of liver cancer.